FRAMEWORK FOR FAST BUILDING SOFTWARE REQUIREMENTS SPECIFICATION - Ponglikit Singchai; Wanchai Rivepiboon (Faculty of Computer Science Universitas Indonesia, 2013)
Software Requirements is an important process in software project. If the information is inaccurate or delayed, the next steps may have problems. If system analyst has the initial or suggestion documents which use software requirements specification of past software projects with similar knowledge, it can help system analyst to building the software requirements specification involves gathering requirements from users more efficient and faster. Therefore, we propose a framework for fast building the relationships of the software requirements specification of past software projects from the similarity of the requirements in each project using Bayesian network model for retrieving requirements with similar knowledge to the new project.